Bambootech drainage innovations - Mohd Yusri, Nur Anis Ayuni; Anuar, Arif Azhan; Sirajuddin, Ahmad Syameel; Mohd Sani, Muhammad Afif Aiman; Mahyuddin, Muhammad Naim (2024)
This innovation intends to replace the materials for making gutters to materials that can be recycled and are easy to find nowadays. Nowadays, the installation of conventional drainage systems can be labour-intensive and costly, particularly in remote or resource-constrained regions. Against this backdrop, the use of bamboo as a drainage material presents an appealing option. Bamboo's intrinsic features, such as strength, resilience, and flexibility, make it ideal for creating drainage channels, culverts, and other water management structures. The installation starts with site assessment and preparation, followed by sourcing sustainable bamboo, treating it for durability, and precise installation to ensure functionality. The findings of the project on bamboo gutters reveal their effective performance in managing rainwater drainage, with comparable durability to traditional materials when properly treated. They require minimal maintenance and show potential cost savings over their lifespan. Bamboo gutters also offer environmental benefits due to bamboo's renewable nature and lower carbon footprint compared to nonrenewable alternatives. Recommendations focus on optimising design and maintenance practices to enhance long-term viability and sustainability. As awareness of environmental impact increases, there is a rising preference for renewable resources like bamboo in construction. Bamboo gutters offer competitive advantages such as lower production costs, reduced environmental footprint, and potential market differentiation in sustainable building practices.